Efforts to Improve Maternal and Child Welfare through Posyandu - Rosi L. Vini Siregar; Yessilia Osira (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Posyandu is a community-based integrated health service post that plays an important role in supporting maternal and child welfare. It is managed and organized by the community with technical assistance from health workers, particularly in providing maternal and child health services, family planning, immunization, nutrition monitoring, and health education. This study aims to describe efforts to improve maternal and child welfare through Posyandu in Kebun Beler Subdistrict, Ratu Agung District, Bengkulu City. This research used a qualitative method with a descriptive approach. Informants consisted of Posyandu cadres, parents, village officials, and community members selected purposively. Data were collected through interviews, observation, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that Posyandu activities in Kebun Beler have been implemented routinely and provide direct benefits for mothers and children. The services include toddler weighing, immunization, supplementary feeding, nutrition counseling, maternal health education, and monitoring of child growth and development. The most dominant aspect of child welfare fulfilled through Posyandu is the right to survival and development. However, several obstacles remain, including limited public trust in vaccines and concerns about side effects after immunization. Therefore, strengthening health education, cadre capacity, and community trust is essential to improve the effectiveness of Posyandu services.